2013
DOI: 10.18632/oncotarget.1745
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib suppresses hepatoma stemness and progression by up-regulating PTEN

Abstract: Celecoxib, a COX-2 inhibitor and non-steroidal anti-inflammatory drug, can prevent several types of cancer, including hepatocellular carcinoma (HCC). Here we show that celecoxib suppressed the self-renewal and drug-pumping functions in HCC cells. Besides, celecoxib depleted CD44 + /CD133 + hepatic cancer stem cells (hCSC). Prostaglandin E2 (PGE2) and CD133 overexpression did not reverse the celecoxib-induced depletion of hCSC. Also, celecoxib inhibited progression of rat Novikoff hepatoma. Moreover, a 60-day c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 51 publications
(65 reference statements)
5
45
0
Order By: Relevance
“…Finally, celecoxib administration did not worsen epirubicin-induced myelotoxicity. Given that celecoxib therapy is safe and well tolerated for HCCbearing animals [17], the present study supports the potential of combined epirubicin and celecoxib therapy for advanced or unresectable HCC.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Finally, celecoxib administration did not worsen epirubicin-induced myelotoxicity. Given that celecoxib therapy is safe and well tolerated for HCCbearing animals [17], the present study supports the potential of combined epirubicin and celecoxib therapy for advanced or unresectable HCC.…”
Section: Discussionsupporting
confidence: 74%
“…Our previous study showed that epirubicin treatment effectively delayed the tumor growth in orthotropic hepatoma model . Moreover, we have also found that celecoxib therapy potently suppressed HCC progression and extended the survival rate of HCC‐bearing rats through depletion of CD44/CD133 hepatic CSCs . But epirubicin or celecoxib monotherapy did not eradicate hepatic tumor and reduce tumor size of established hepatoma in our previous researches.…”
Section: Introductionmentioning
confidence: 82%
“…Nevertheless, the association is quite remarkable. Given the newly available and effective therapies for hepatitis B and C (and possibly also anti-inflammatory agent, such as aspirin, NSAIDS, Cox inhibitors, in patients without bleeding disorder), it may be that their use in suppressing hepatic inflammation and/or improving liver function in HCC patients with inflamed livers, offer the possibility of decreasing HCC aggressiveness through improvement of the underlying liver function [28][29][30][31][32]. What might be the mechanisms by which liver function parameters could influence HCC aggressiveness Two possible general explanations might be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, COX-2 is widely expressed and profoundly linked to poor prognosis in a variety of malignant tumors [12, 13]. What's more, inhibition of COX-2 has a reversed effect on cancer progression [1418]. Therefore, COX-2 might be a potential prognostic factor to predict the survival in patients with cancers.…”
Section: Introductionmentioning
confidence: 99%